Singapore : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2001)
The major objectives of the banking system reform are twofold: first, to continue to gradually open domestic banks to greater competition from foreign banks, and second, for Singapore banks to retain significant domestic market share in this more open environment as well as to become significant participants in the regional market. The authorities have clearly stated that they see the process of mergers and consolidation of the local banks as inevitable, but that they do not intend to force the process.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet